Emerging Roles for Hox Proteins in the Last Steps of Neuronal Development in Worms, Flies, and Mice - Feng, Weidong; Li, Yinan; Kratsios, Paschalis (Frontiers in Neuroscience, 2022)
A remarkable diversity of cell types characterizes every animal nervous system. Previous studies provided important insights into how neurons commit to a particular fate, migrate to the right place and form precise axodendritic patterns. However, the mechanisms controlling later steps of neuronal development remain poorly understood. Hox proteins represent a conserved family of homeodomain transcription factors with well-established roles in anterior-posterior (A-P) patterning and the early steps of nervous system development, including progenitor cell specification, neuronal migration, cell survival, axon guidance and dendrite morphogenesis. This review highlights recent studies in C. elegans, Drosophila melanogaster and mice that suggest new roles for Hox proteins in processes occurring during later steps of neuronal development, such as synapse formation and acquisition of neuronal terminal identity features (e.g., expression of ion channels, neurotransmitter receptors and neuropeptides). Moreover, we focus on exciting findings suggesting Hox proteins are required to maintain synaptic structures and neuronal terminal identity during post-embryonic life. Altogether, these studies, in three model systems support the hypothesis that certain Hox proteins are continuously required, from early development throughout post-embryonic life, to build and maintain a functional nervous system, significantly expanding their functional repertoire beyond the control of early A-P patterning.